Detection of SARS-CoV-2 in the gastrointestinal tract among patients with negative nasopharyngeal COVID-19 testing prior to endoscopy - Yang, Dennis; Perbtani, Yaseen B.; Loeb, Julia; Liu, Nanlong; Draganov, Peter V.; Estores, David E.; Lauzardo, Michael; Maurelli, Anthony; Lednicky, John A.; Morris, J. Glenn (Endoscopy International Open, 2021)
Background and study aims The clinical significance of SARS-CoV-2 RNA in the stool remains unclear. We aimed to determine whether SARS-CoV-2 is detected via real-time reverse transcriptase polymerase chain reaction (rRT-PCR) in the gastrointestinal tracts of patients scheduled for endoscopy and if the virus obtained from these clinical specimens could be isolated in culture.Patients and methods All patients underwent symptom screening and had negative nasopharyngeal testing for SARS-CoV-2 within 72 hours of their scheduled procedure. Study samples were collected via nasopharyngeal swab, rectal swab, and fluid from the upper gastrointestinal tract and/or colon based on their endoscopic procedure(s). Samples were tested for SARS-CoV-2 via rRT-PCR. SARS-CoV-2 positive specimens were isolated and cultured in Vero-E6 cells.Results 243 patients (mean age 63.1 years;54.3 % men) were enrolled from July 15, 2020 to September 2, 2020. SARS-CoV-2 testing was performed from 242 (99.6 %) nasopharyngeal, 243 (100 %) rectal, 183 (75.3 %) upper gastrointestinal tract and 73 (30 %) colon samples. SARS-CoV-2 RNA was detected in the nasopharynx and gastrointestinal specimens in one patient (0.4 %). After a 14-day incubation period, there was no evidence of virus growth in cells incubated with any of these specimens.Conclusions SARS-CoV-2 was rarely detected in the gastrointestinal tract of patients with negative nasopharyngeal testing prior to endoscopy. No live virus was detected by culture, further highlighting that presence of viral genome on its own is not sufficient proof of infectivity. PCR-based screening provides limited insight into virus infectivity and its results should be interpreted carefully as to avoid unnecessary delays in clinical care or inadvertent risk exposure.